El cine ‘CliFi’ y la rentabilidad de salvar el planeta. Análisis de los contextos de producción, distribución y exhibición en España entre 2000 y 2019 - Dr. David VICENTE TORRICO (Fonseca, Journal of Communication, 2023)
Twenty-first century society is facing the climate emergency, a scientific phenomenon that has been strongly incorporated into the political, media and social spheres. Its inclusion in the UN Development Goals, the increase in news coverage and the recent mobilization of citizens have acted as catalysts for a narrative traditionally marked by more shadows than lights. In our research we propose an agenda study on the incorporation of the 'CliFi' (climate fiction) content in Spanish movie theatres between 2000 and 2019.